Vogal temática em P4 de verbos regulares de primeira conjugação: estudo da variação morfofonológica no noroeste paulista - Cruziniani, Fátima Elis (Universidade Estadual de Ponta Grossa, 2025)
Infectious diseases are illnesses caused by pathogens, including viruses and bacteria. They can be transmitted from one person to another, from animals to humans, or between animals. Avian influenza, also known as bird flu, spreads among wild birds and domestic poultry and can be transmitted to some mammalian species, including humans. These diseases continue to cause a significant threat to public health and animal production, especially when they involve agents with zoonotic potential, such as the avian influenza virus. In this dissertation, compartmental epidemiological models are explored to mathematically describe and analyze the transmission dynamics of diseases, with a focus on avian influenza among birds and its potential spread to humans. Initially, a review of the main classical compartmental models, such as SI, SIR, SIS, SIRS, and SEIR, is presented, with emphasis on the biological interpretation of the involved parameters and the analysis of the stability of equilibrium points. Next, a coupled SI-SIR model is studied, which represents the interaction between a bird population and a human population. Qualitative analyses of the system are executed, including the calculation of the basic reproduction number, as well as numerical simulations that identify different epidemiological scenarios depending on the considered parameters. Furthermore, seasonal forcing is incorporated into the transmission rate of the disease, substantially increasing the dynamic complexity of the system. The obtained results demonstrate that controlling the disease in the bird population is essential to prevent outbreaks in humans, highlighting the importance of surveillance and containment strategies in animal production environments.
Keywords: Doenças infecciosas; Epidemia; Modelagem matemática; Gripe; Sazonalidade